A new Trunk Rot species in the genus Kretzschmaria (Xylariaceae) from Guangxi, China - Lu, Changtao; Hu, Hongmin; Habib, Kamran; Ren, Yulin; Kang, Yingqian; Shen, Xiangchun; Li, Qirui; Long, Qingde (Phytotaxa, 2024)
Kretzschmaria shiwandashanensis sp. nov. is described and illustrated from the tropical forests of Shiwandashan National Nature Reserve in Guangxi, China. The new taxon is characterized by stromata with narrow connective tissues, crenate sloped margins, distinctive cracks on the surface, and relatively small ascospores. According to phylogenetic analysis of combined internal transcribed spacers (ITS), alpha actin (ACT), beta-tubulin (TUB2) and RNA polymerase II second largest subunit sequences (rpb2), the new species is closely related to K. sandvicensis, from which it is distinguished by its smaller perithecia and ascospores that are shorter and broader. Descriptions, illustrations, and phylogeny of the new species are provided.